Exploring Digital Health Innovations Across Africa: Challenges, Opportunities and the Way Forward - Oladosu, Micheal Abimbola; Abah, Moses Adondua; Ebeledike, Kosiso Patience; Onuorah, Uju Maryanne; Okoye , Sandra Chiamaka; Adebisi, Kehinde Adebola; Oladosu, Olaide Ayokunmi; Ekele , Angel Ojimaojo (Journal of Health Informatics in Africa, 2026)
Objectives: To systematically review the current state, applications, barriers, and outcomes of digital health technologies across Africa, and to identify opportunities for enhancing healthcare delivery through digital innovation. Design: Systematic review following PRISMA guidelines. Methods: A comprehensive search was conducted across PubMed, Scopus, Web of Science, African Journals Online, and Google Scholar databases from 2014-2025. Search terms included "digital health," "mHealth," "telemedicine," "electronic health records," "artificial intelligence," and "Africa." Studies were included if they focused on digital health interventions, implementation, or outcomes in African countries. Results: Sixty-eight studies from 32 African countries were analyzed. Mobile health (mHealth) represented 45% of interventions, telemedicine 28%, electronic health records 18%, and artificial intelligence 9%. Key applications included maternal and child health (34%), infectious disease management (29%), and chronic disease monitoring (21%). Major barriers included inadequate infrastructure (78% of studies), limited digital literacy (65%), and financial constraints (59%). Success factors included stakeholder engagement (82%), appropriate technology selection (76%), and integration with existing systems (71%). Conclusions: Digital health technologies demonstrate significant potential for transforming healthcare delivery across Africa. However, successful implementation requires addressing infrastructure limitations, enhancing digital literacy, ensuring sustainable financing, and developing context-appropriate solutions. Strategic investments in enabling infrastructure and capacity building are essential for realizing the full potential of digital health in Africa.